Molecular phylogeny and morphology reveal a new wood-inhabiting fungal species, Mycobernardia tenuis (Corticiaceae, Corticiales) from China - Wang, Hongjuan; Deng, Yinglian; Liu, Yu; Liu, Linfeng; Chen, Meng; Zhao, Changlin (Phytotaxa, 2025)
Taxonomy plays a central role in understanding the diversity of life, translating the products of biological exploration and discovery—specimens and observations—into systems of names that establish a “classification home” for taxa. In this study, a new species, Mycobernardia tenuis is proposed based on a combination of morphological features and molecular evidence. Mycobernardia tenuis is characterized by membranaceous, reticular basidiomata with white to slightly cream hymenial surface, a monomitic hyphal system with clamped generative hyphae, subcylindrical to subclavate basidia, allantoid basidiospores measuring 6–8.5 × 2–3.5 µm. The phylogenetic tree inferred from ITS+nLSU sequences revealed that Mycobernardia tenuis is nested within the family Corticiaceae of the order Corticiales, where it forms a sister species to M. incrustans and is closely related to M. yunnanensis. A full description, illustrations, and phylogenetic analysis results of the new species are provided.